ANALISIS SKALA USAHATANI CABE RAWIT VARIETAS JUWITA DI KECAMATAN PRINGGERATA KABUPATEN LOMBOK TENGAH - MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA; THERESIA SUZANNA CATHARINA (GANEC SWARA, 2018)
Adoption of new technologies such as the use of chili seeds from superior varieties Juwita, needs to consider the social and economic aspects. Socially, the technology can be implemented by the farmers, and economically the farming should be able to provide proper benefits for the farmers and their families.The purpose of this research is to analyze the scale of chili farming of superior Juwita varieties in Pringgerata sub-district, Lombok Tengah regency, by setting 60 respondents in non proportional random sampling and data analysis using Cobb-Douglas function analysis, followed by F and T test.The results show that: 1). Chili farming of Juwita varieties is on an increasing production scale (increasing Return To Scala). This bi =å proves the elasticity of production is greater than one ie ( 4,426)> 1, which means that if the use of input is added then the proportion of additional production will be greater than the proportion of the input addition, 2). Simultaneously that the factors of production (land area, seed, fertilizer, pesticide, and labor) have a significant effect on production level. This can be seen from the results of model testing using Cobb-Douglas production function obtained F hit (31,921)> F tab (Z 1,645 = 0.95), and the value of determination coefficient (R2) of 0.864 which means that the magnitude of the influence of independent variables against dependent variable of 86.4%, while the remaining 13.6% is influenced by other factors outside the model, 3). Partially, the factor of production of land, seed, fertilizer and labor have a significant effect on production level (t hit> t table), while pesticide has an effect on production level but not significant (t hit <t table)